Non-viral strategies for ocular gene delivery - V. Oliveira, Ana (2019)
The success of gene therapy relies on efficient gene transfer and stable transgene expression. The in vivo efficiency is determined by the delivery vector, route of administration, therapeutic gene, and target cells. While some requirements are common to several strategies, others depend on the target disease and transgene product. Consequently, it is unlikely that a single system is suitable for all applications. This review examines current gene therapy strategies, focusing on non-viral approaches and the use of natural polymers with the eye, and particularly the retina, as their gene delivery target. (C) 2017 Elsevier B.V. All rights reserved.